Wake Forest Men's Tennis Team - Bunn (Z. Smith Reynolds Library, 1970)
No date on photo
Jasper Memory talks to tennis player beside net.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth